M3 Money Demand and Excess Liquidity in the Euro Area - Christian Dreger; Jürgen Wolters (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Money growth in the euro area has exceeded its target since 2001. Likewise, recent empirical studies did not find evidence in favour of a stable long run money demand function. The equation appears to be increasingly unstable if more recent data are used. If the link between money balances and the macroeconomy is fragile, the rationale of monetary aggregates in the ECB strategy has to be doubted. In contrast to the bulk of the literature, we are able to identify a stable long run money demand relationship for M3 with reasonable long run behaviour. This finding is robust for different (ML and S2S) estimation methods. To obtain the result, the short run homogeneity restriction between money and prices is relaxed. In addition, a rise in the income elasticity after 2001 is taken into account. The break might be linked to the introduction of euro coins and banknotes. The monetary overhang and the real money gap do not indicate significant inflation pressures. The corresponding error correction model survives a battery of specification tests.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C22; C52; E41; 330; Cointegration analysis; error correction; excess liquidity; money demand; monetary policy